Solve the linear equation m - $$\frac{m-1}{2} = 1 - \frac{m-2}{3}$$

Asked by Aaryan | 1 year ago |  66

##### Solution :-

m - $$\frac{m-1}{2} = 1 - \frac{m-2}{3}$$

L.C.M. of the denominators, 2 and 3, is 6.

Multiplying both sides by 6, we obtain

6m - 3(m - 1) = 6 - 2(m - 2)

⇒ 6m - 3m + 3 = 6 - 2m + 4 (Opening the brackets)

⇒ 6m - 3m + 2m = 6 + 4 - 3

⇒ 5m = 7

⇒ m = $$\frac{7}{5}$$

Answered by Sakshi | 1 year ago

### Related Questions

#### Solve the inequations and graph their solutions on a number line  – 1 < (x / 2) + 1 ≤ 3, x ε l

Solve the inequations and graph their solutions on a number line  – 1 < ($$\dfrac{x}{2}$$) + 1 ≤ 3, x ε l

#### Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

#### Solve (x / 3) + (1 / 4) < (x / 6) + (1 / 2), x ε W. Also represent its solution on the number line.

Solve ($$\dfrac{x}{3}$$) + ($$\dfrac{1}{4}$$) < ($$\dfrac{x}{6}$$) + ($$\dfrac{1}{2}$$), x ε W. Also represent its solution on the number line.

If the replacement set is {-3, -2, -1, 0, 1, 2, 3}, solve the inequation $$\dfrac {(3x – 1) }{2} < 2$$. Represent its solution on the number line.
Solve the inequations ($$\dfrac{3}{2}$$) – ($$\dfrac{x}{2}$$) > – 1, x ε N